STRATEGI PENGEMBANGAN DESA WISATA PULESARI SEBAGAI DAYA TARIK WISATA DI SLEMAN, YOGYAKARTA - Syaifulloh, Muhammad (Kepariwisataan: Jurnal Ilmiah, 2017)
Pulesari tourism village is one of the tourism village in Sleman, Yogyakarta. As a tourism village, it has a lot of tourism potential as beautiful river, historic cave, Sebagai salah satu desa wisata, dusun pulesari banyak menyimpan potensi zallaca garden, zallaca dance, kubro siwo dance, pager bumi ceremony and sadranan ceremony. That potential can be fascination for tourist, but it was needed community participation as human resource and government. This is in line with the motto "from community and for community". To manage and develop the tourism potential required Pulesari Hamlet needed right strategy. Therefore we need research using SWOT analysis to determine the strengths, weaknesses, opportunities and threats faced by the tourist pulesari village. From the results of the SWOT analysis, can be used as consideration to make a decision, so that could be a leading tourist village in Yogyakarta and can improve the local economy. Keywords: Pulesari village, SWOT, Community Based Tourism (CBT)